RELEVANSI ANTARA PEMIDANAAN INDONESIA DAN SANKSI PIDANA ISLAM - Syatar, Abdul (Jurusan Syariah dan Ekonomi Islam Institut Agama Islam Negeri (IAIN) Parepare, 2018)
Abstract: Positive crimes and Islamic crimes are the same in terms of determining a crime and violation. The difference lies in the aspect of punishment which is known as punishment. Although there is an element of difference between the two, it has a point of relevance of objectives between Indonesian criminal sanctions and Islamic criminal sanctions. This is especially related to the divine value between Islamic criminal sanctions and Indonesian criminal sanctions. The right of Allah swt. contained in the application of Islamic criminal sanctions is one of the teachings of Islam. However, in the application of punishment in the Indonesian legal system it still included divine elements because the source of Indonesian law, namely Pancasila and the 1945 Constitution, accommodated the divine spirit. Indonesian Criminal Law has Islamic legal values ​​in the form of divine value, education and maintaining stability in society. Thus, the peak of relevance between Islamic criminal sanctions and Indonesian criminal sanctions together requires the issue of maintaining stability in society. It is time for Muslims to unite in terms of discussing the inclusion of Islamic criminal law sanctions into the renewal of Indonesian criminal and criminal prosecution.   Abstrak: Pidana positif dan pidana Islam sama dalam hal menentukan sebuah kejahatan dan pelanggaran. Perbedaan terletak pada aspek pemberian hukuman yang dikenal dengan pemidanaan. Walaupun ada unsur perbedaan dari keduanya, tetapi memiliki titik relevansi tujuan antara pemidanaan Indonesia dan sanksi pidana Islam. Hal yang terkait terutama dalam nilai ilahiyah antara sanksi pidana Islam dan pemidanaan Indonesia. Hak Allah swt. yang termuat dalam keberlakuan sanksi pidana Islam merupakan salah satu ajaran Islam. Akan tetapi, dalam keberlakuan pemidanaan dalam sistem hukum Indonesia pun masih memasukkan unsur ilahiyah karena sumber hukum Indonesia yaitu Pancasila dan UUD 1945 mengakomodir spirit ketuhanan. Pemidanaan Indonesia memiliki nilai-nilai hukum Islam berupa nilai ilahiyah, pendidikan dan menjaga stabilitas dalam masyarakat.. Dengan demikian, puncak relevansi antara sanksi pidana Islam dan pemidanaan Indonesia sama-sama menghendaki persoalan menjaga stablitas dalam masyarakat. Sudah saatnya umat Islam bersatu dalam hal mewacanakan untuk memasukkan sanksi hukum pidana Islam ke dalam pembaharuan pemidanaan dan pidana Indonesia.